Behavioral of Customer Loyalty on E-Commerce: The Mediating Effect of E-Satisfaction in Tiktok Shop - Lova, Anggil Nopra; Indra Budaya (Kirana Publisher (KNPub), 2023)
This study aims to find out and explain how the effect of e-service quality and e-recovery service quality on e-customer loyalty when online shopping is mediated by e-customer satisfaction at Tiktok shop, both directly and indirectly. this research is quantitative. The sampling method used was purposive sampling with a research instrument in the form of a questionnaire which was distributed to 280 respondents who had used the Tiktok shop service. The results showed that the e-services qaulity and recovery services quality had a direct effect on e-customer satisfaction and e-customer loyalty. E-satisfaction has an important role in mediating the relationship between e-service quality and recovery service quality on e-customer loyalty. Therefore, an e-commerce must be able to make customers satisfied by providing good e-service quality and recovery service quality in the event of a service failure by the company, learning from these findings we must maintain customer satisfaction in terms of customer service so that these customers remain loyal and do not switch to competitors